Novels and stories - Hurston, Zora Neale (Libr. of America, 1995)
Part of a two-volume set of works by Zora Neale Hurston, Novels and Stories features the acclaimed 1937 novel Their Eyes Were Watching God– plus Jonah's Gourd Vine, Moses Man of the Mountain, Seraph on the Suwanee, and selected stories. Includes a newly researched chronology of Hurston's life, detailed notes, and a brief essay on the texts.
Enth.: Jonah's gourd vine. Their eyes were watching God. Moses, man of the mountain. Seraph on the Suwanee. Selected stories
Keywords: Hurston; Zora Neale; Jonah's gourd vine; Their eyes were watching God; Schwarze. USA; African Americans